Interracial unions and sleep duration among heterosexual American adults. (September 2022) - Lopez, Angelica; Sheehan, Connor; Yahirun, Jenjira
Abstract: For Americans in romantic unions, sleep occurs in the context of couple relationships. Romantic partners influence one another's circadian rhythms, share beds, buffer or cause stress, and share resources that can be used to improve sleep. Moreover, sleep among individuals in interracial relationships may be negatively impacted by the social construction of race/ethnicity that drive health disparities and that point to the importance of factors such as racism, stress and social adversity that represent the unique lived reality of interracial couples in the U.S. Using non-dyadic data from the 2004–2018 National Health Interview Survey (n = 243, 552) we fit a series of multinomial regression models predicting self-reported sleep duration of six or fewer (short), seven to eight (normal), and nine or more (long) hours. After adjusting for demographics, household socioeconomic characteristics, and health characteristics/behaviors, we find that individuals in interracial unions report significantly higher odds of short sleep compared to normal sleep. Race/ethnic stratified models indicated that all respondents in interracial relationships had higher odds of reporting short sleep, but that the association was particularly pronounced among non-Hispanic White adults and Hispanic adults. Generally, we find few differences in these associations between men and women or between those in marital versus those in cohabiting relationships. Future research should continue to investigate how social inequality conditions sleep for Americans in romantic relationships. Highlights: Sleep is a dyadic process among romantic couples. Individuals in interracial unions were more likely to report short sleep. Non-Hispanic White adults in interracial unions reported short sleep. Hispanic adults in same-race unions reported high levels of normal sleep. Gender did not moderate the link between short sleep and interracial unions.